Perancangan Poster Carousel Sebagai Media Dakwah Berbasis Digital (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2025)
In the continuously evolving digital era, preaching media is becoming increasingly vast and dynamic. One medium with significant potential is digitally-based posters. This research aims to identify and analyze the design strategies for digital-based posters as an effective medium for preaching. Through a qualitative approach and design study, the authors explore various design aspects, including the selection of illustrations, typography, and color that influence the success of the preaching message.